An exploration into the effects of thematic-fantasy play on Year 1 children’s ability to write a recount of the featured story. - Burt, Louisa (2017)
Due to a surge in my school’s Reception intake last September, and the resultant restructuring of classes across the Infants, I found myself forced to adapt my pedagogies to meet the learning needs of both Reception and Year 1 pupils. Since this involved reassessing the role of play within my classroom, I became aware of the current tension between proponents of play-based learning beyond the Foundation Stage and advocates of increased formality; particularly in relation to the efficacy of play in supporting literacy achievement. This dissertation, therefore, explores the effects of thematic-fantasy play on Year 1 children’s ability to write a recount of the featured story. By comparing the written recounts of a sample of fifteen children with my observations of their behaviours and use of language during a thematically linked role-play session, I was able to isolate narrative proficiency, as opposed to language skill, as the chief aspect of writing development most likely to benefit from a socio-dramatic play intervention. However, the unexpected discovery that even children as old as six can lack the maturity to engage in truly cooperative play has implications for my deployment of such approaches in future.